A prospective diagnostic study on the use of narrow band imaging on suspiscious lesions during colonoscopic examination in Hospital Universiti Sains Malaysia - Yaacob, Huzairi (2013)
BACKGROUND: Colonoscopy is the gold standard to detect colorectal neoplasm. There have been multiple attempts to improve diagnostic accuracy partly by image improvement and one of them is narrow band imaging. Based on published reports that NBI have the good diagnostic accuracy, the usage of NBI in differentiating neoplastic and non-neoplastic colorectal lesions was carried out in our hospital (HUSM) for the first time. OBJECTIVE: To explore the diagnostic validity of NBI colonoscopy as well as associated factors related to the neoplastic and non-neoplastic colorectallesions. METHOD: One hundred patients who came mainly for screening colonoscopy with variable lower gastrointestinal symptoms that have suspicious colorectal lesions were included in this study. Only one ofthe most suspicious lesions in each patient (n=IOO) was analyzed using NBI colonoscopy based on Sano' s classification. These lesions were then either biopsied or resected for histopathological analysis. Endoscopic images were captured electronically and allocated for single reader evaluation. Sensitivity, specificity and diagnostic accuracy of the NBI colonoscopy was assess by comparing it to histopathology results. Other associated factors related to neoplastic and non-neoplastic lesions were analyzed accordingly. RESULTS: ROC analysis showed that the sensitivity and specificity of the NBI were 88.2% and 71.9% respectively. The analysis also showed that the area under ROC was 0.801, indicating good level of discriminative ability of NBI to differentiate between disease and non-disease. Bowel preparation failed to reach significant association with NBI outcomes; therefore this study suggests that suboptimal bowel preparation is adequate to obtain good outputs of NBIcolonoscopy. There were significant association between LOW and site of lesions to the HPE outcomes even after controlling other variables (p<O.OS). CONCLUSION: Our study has shown that NBI system In colonoscopy was capable of distinguishing neoplastic from non-neoplastic colorectal lesions. It indicates an acceptable level of agreement with the gold-standard (i.e. HPE). However the role of NBI in screening and surveillance in Malaysia still need further evaluation and exploration.